Intransigencia y tolerancia religiosa en el primer liberalismo español - Emilio La Parra López (Mélanges de la Casa de Velázquez)
This article examines the extent to which the principle of religious intolerance was espoused by the first Spanish liberals, taking into account that intolerance was an essential ingredient of Spanish political culture in the time-frame considered, that is the early 19th century. Unlike the royalists or «serviles», liberals did not see intolerance as an immovable principle intrinsic to Catholicism, but as a precept of civil power which that power could modify whenever it saw fit. From that viewpoint the article asks why it was not considered convenient to debate toleration at that time. It offers an interpretation of Article 12 of the Constitution of 1812 and shows how in the course of the parliamentary debates the liberals moderated the intolerance of creeds implicit in that article.